TRANSFORMATION OF LIFE NEEDS MEETMENT BASED ON LAKES AND SAGO FORESTS IN THE NENDALI COMMUNITY IN EAST SENTA - Annisa Nurjanah; Agung Dwi Bagus Ramadhani; Ansari (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study examines the transformation of livelihood strategies among the Nendali community in East Sentani District, Jayapura Regency, Papua Province, whose subsistence system has historically depended on Lake Sentani's ecosystem and sago palm forests. Over centuries, both natural resources have served not merely as economic foundations but also as cultural anchors and social bonds for the community. However, rapid infrastructure development, large-scale land conversion, and the expanding penetration of market-based economies have forced the local population to fundamentally readjust their livelihood orientations. Using a qualitative ethnographic approach, this research finds that a multidimensional shift has occurred from nature-based subsistence systems toward economic diversification involving trade, services, and wage labor. These changes have further implications for gender relations, the continuity of local ecological knowledge, and the effectiveness of customary institutions in managing natural resources. This study underlines the urgency of integrating Nendali's indigenous wisdom with more responsive and socially just regional development policies.